Proposal of a screening instrument for autism spectrum disorder in children (Mini-TEA Scale) - Cassiano Mateus Forcelini; Regina Ampese; Helena Younes de Melo; Camila Pereira Neubauer Pasin; José Renato Donadussi Pádua; Camila Boschetti Spanholo; Francine Ehrhardt Hoffmann; Júlia Breitenbach Diniz; Laís Cristine Zanella Capponi; Luiza Souza; Maxciel Zortea (Arquivos de Neuro-Psiquiatria)
Background Autism spectrum disorder (ASD) requires trained professionals for its adequate diagnosis. There is a shortage of such professionals in Brazil. Screening tools could identify priority cases. The only instrument for that in Brazilian Portuguese is employed for toddlers up to 2.5 years old.